Assessment of factors controlling clumped isotopes and [Delta]18O values of hydrothermal vent calcites - Kluge, Tobias (Geochemistry, geophysics, geosystems, 2018)
The clumped isotope composition of CaCO3 (Δ47) is a geochemical proxy that can provide mineral formation temperatures and, together with measured carbonate δ18O, inferred fluid δ18O values. Under natural conditions, carbonates form within a relatively wide pH range and varying growth rates which are typically not reflected in laboratory-based calibrations (mostly ∼pH 8, moderate growth rates). A pH and growth-rate dependence is known for oxygen isotopes and was also postulated for clumped isotopes. Theoretical predictions suggest that Δ47 values could lie between the carbonate equilibrium value and the value inherited from the dissolved inorganic carbon (predicted offset: +0.04‰ pH < 4 and −0.025‰ at high pH > 12). Here we test whether pH (in addition to temperature) is recorded in the carbonate clumped isotope composition using modern calcites from natural travertine-forming streams and scales precipitated in pipes of deep geothermal wells from Italy, Hungary, and Turkey (pH: 6.1-7.5, T: 33-100°C). Although a comparison of all samples with expected equilibrium values in this pH range and known formation temperatures reveals only an insignificant Δ47 offset (0.006 ± 0.004‰, 1SE, n = 9), the clumped isotope values of samples with the highest growth rates (0.014 ± 0.007‰, 1SE, n = 5) are consistent with the theoretical prediction attributable to pH of 0.01‰. Similarly, deviations in δ18O of up to −2‰ follow a growth-rate dependence. This field-based study shows that pH-related effects are mostly small for Δ47 in the subsurface environment at lower pH and that high mineral growth rates control the magnitude of this disequilibrium.